The Role of Islamic Families in Overcoming the Moral Degradation of Teenagers at Kaliombo Kulon Hamlet Kaliombo Village Rembang Regency - Linda Wahyuningtyas; Mukhlis Fathurrohman (Bulletin of Science Education, 2024)
This research aims to determine the role of Islamic families in overcoming the moral degradation that occurs among teenagers in Kaliombo Kulon Hamlet in 2024. Moral degradation is the decline or fading of the values ​​and morals that apply in society. This research uses qualitative methods with a descriptive approach. In collecting data, researchers used observation, interviews and documentation methods. Data analysis in this research uses the Miles and Huberman model with four stages, namely data collection, data reduction, data presentation and conclusions. Meanwhile, the validity of the data in this research uses a data credibility test with data triangulation. The research results revealed two main findings. First, moral degradation among teenagers in Kaliombo Kulon Hamlet can be seen in the form of impolite behavior such as harsh words, smoking habits and disrespect. Several factors that influence this behavior include the influence of the friendship environment, lack of supervision from parents, and lack of religious education. Second, the role of parents in overcoming moral degradation is very important and includes various actions, such as providing wise advice, maintaining open communication between parents and teenagers, fostering religious values, and being a good role model for their children. This research confirms that the family has a central role in guiding teenagers to have good morality amidst current social challenges. With the right role, Muslim families can help teenagers face the negative influences of their environment and form better characters.